Structures and properties of buffer layers with nanometer thickness for PBCMO/YBCO epitaxial multilayers. (2018) - Tipparach, U.; Chen, T.P.; Sricheewin, C.
Abstract: Insulator buffer layer materials, PrBa2 (Cu1-xMx )3 O7 -δ (PBCMO), with M = Al and Ga with different portions were synthesized to improve better buffer-layer materials for fabricating superconducting devices from YBa2 Cu3 O7 -δ (YBCO) superconductor. Neutron and X-ray diffraction data reveal that the structures of PBCMO and YBCO are the same and their lattice parameters are well matched, while the resistivity shows that PBCMO have much higher resistivity than PrBa2 Cu3 O7 (PBCO). Epitaxial multilayers of PBCMO/YBCO were fabricated by laser ablation to explore the effect of PBCMO layer thickness on YBCO superconducting layers. Superconductivity was not found above 4.2 K for one unit cell thickness of YBCO. As the thickness of PBCMO was varied with constant thickness of YBCO films, the transition temperature of the multilayers remains unchanged even though the PBCMO layer is made as thin as the unit cell of 12.5Å. The difference indicates that PBCMO is better buffer layer and is adequate to insulate YBCO films in the multilayers and to cut off the superconducting coupling between YBCO layers.